Movable oven for bread baking intended for food preparation in Serbian Army peace corps - Tešanović, Branko M.; Jović, Saša B. (Vojnotehnički glasnik / Military Technical Courier, 2014)
An oven for baking bread in field conditions is assigned to units that are by their nature relatively stationary and whose size does not require a movable bakery. It is intended for baking bread in our units located in international missions with supply difficulties, since our units have a habit od consuming bread instead of biscuits. The oven is of a prefabricated type, adapted for use in all types of terrains, simple design which makes it possible to be, dismantled and easyly transported. Introduction Changes in the socio-political environment have shown that it is not cost- effective to have an army whose sole task in peacetime would be to prepare for any defense from external enemies. Engagement of the Serbian Armed Forces in tasks with foreign missions imposes the need for integrated nutrition with armed forces of other countries. Production of bread, which predominantly affects the eating habits of the Serbian Armed Forces, requires the investigation of a possibility of its production. In conditions of supply difficulties, the use of movable ovens for baking bread can contribute to a more regular supply of bread to Serbian Army members who participate in peacekeeping operations. Eating habits In the period of the Principality of Serbia, the dominant share in daily rations was bread, which can be attributed to the poor economic situation of the Principality of Serbia. The recipe for military bread dates from 1883. During World War II, the bread share military daily rations was 40%, while today it accounts for 18.5%. The assessement of bread requirements depends not only on its energy value and weight, which is undoubtely important, but also on eating habits. Field oven A movable field oven is designed for baking bread under various climatic and terrain conditions in all three missions of the Army. The oven capacity is 68 kg of bread in one serving, and the daily capacity is 1420 kg. The oven set consists of a prefabricated body, additional materials, supplies, equipment, tools and tents for protection when working in field conditions. The oven prefabricated body consists of the following parts: feet (front and back), sides (front and rear), tubes (connecting and separating), slats, carriers (transversal, front and the one of the oven door), oven door and chimney. Constructing an oven includes the preparation phase, assembling the prefabricated elements and masonry work. Handling during use includes making fire and baking bread. A 600 g loaf is baked in 25 to 30 minutes. Conclusion The diet of Army members should include semi-wholegrain bread made of 850-type flour that has a higher nutritional value compared to white bread. A field oven of a prefabricated type is suitable for baking bread in units located in international missions.